Dramatic Structure and Development of Randai Sutan Maradewa in Nagari Anduriang, Padangpariaman - Martini, Martini; H, Afrizal (Institut Seni Indonesia Padangpanjang, 2024)
Dramatic Structure and Development of Randai Sutan Maradewa in Nagari Anduriang, Kayu Tanam—Kabupaten. Padang Pariaman discusses the dramatic randai of Sutan Maradewa and its development in Nagari Anduriang. The main objective of the research that underlies this thesis is to examine the dramatic structure and development. The primary data of the research is Sutan Maradewa's randai manuscript which is seen and analyzed with the theory of dramatic structure. This study aims to examine the elements that make up randai, then proceed to reading the history, development, and creation of randai